Cardioprotective effects of Prolame and SNAP are related with nitric oxide production and with diminution of caspases and calpain-1 activities in reperfused rat hearts - Román-Anguiano, Nadia Giovanna; Correa, Francisco; Cano-Martínez, Agustina; de la Peña-Díaz, Aurora; Zazueta, Cecilia (PeerJ, 2019)
Cardiac tissue undergoes changes during ischemia-reperfusion (I-R) that compromise its normal function. Cell death is one of the consequences of such damage, as well as diminution in nitric oxide (NO) content. This signaling molecule regulates the function of the cardiovascular system through dependent and independent effects of cyclic guanosine monophosphate (cGMP). The independent cGMP pathway involves post-translational modification of proteins by S-nitrosylation. Studies in vitro have shown that NO inhibits the activity of caspases and calpains through S-nitrosylation of a cysteine located in their catalytic site, so we propose to elucidate if the regulatory mechanisms of NO are related with changes in S-nitrosylation of cell death proteins in the ischemic-reperfused myocardium. We used two compounds that increase the levels of NO by different mechanisms: Prolame, an amino-estrogenic compound with antiplatelet and anticoagulant effects that induces the increase of NO levels in vivo by activating the endothelial nitric oxide synthase (eNOS) and that has not been tested as a potential inhibitor of apoptosis. On the other hand, S-Nitroso-N-acetylpenicillamine (SNAP), a synthetic NO donor that has been shown to decrease cell death after inducing hypoxia-reoxygenation in cell cultures. Main experimental groups were Control, I-R, I-R+Prolame and I-R+SNAP. Additional groups were used to evaluate the NO action pathways. Contractile function represented as heart rate and ventricular pressure was evaluated in a Langendorff system. Infarct size was measured with 2,3,5-triphenyltetrazolium chloride stain. NO content was determined indirectly by measuring nitrite levels with the Griess reaction and cGMP content was measured by Enzyme-Linked ImmunoSorbent Assay. DNA integrity was evaluated by DNA laddering visualized on an agarose gel and by Terminal deoxynucleotidyl transferase dUTP Nick-End Labeling assay. Activities of caspase-3, caspase-8, caspase-9 and calpain-1 were evaluated spectrophotometrically and the content of caspase-3 and calpain-1 by western blot. S-nitrosylation of caspase-3 and calpain-1 was evaluated by labeling S-nitrosylated cysteines. Our results show that both Prolame and SNAP increased NO content and improved functional recovery in post-ischemic hearts. cGMP-dependent and S-nitrosylation pathways were activated in both groups, but the cGMP-independent pathway was preferentially activated by SNAP, which induced higher levels of NO than Prolame. Although SNAP effectively diminished the activity of all the proteases, a correlative link between the activity of these proteases and S-nitrosylation was not fully established.
Keywords: Cell death; Reperfusion; Caspases; Calpain; Nitric oxide; S-nitrosylation